Ennis Franciscan Friary, loose fragments, hood - O'Donovan, Danielle (My University, 2008)
Fragment of tomb niche like those in north nave wall. Hood moulding comprises from upper face to inner: broad fillet, ogee, hollow chamfer.
Tomb niche
Keywords: Architecture, Gothic -- Ireland; Ennis (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Funerary monuments; Late Medieval; moldings, hollow; moldings, ogee